Bilingual access of single and paired words in the context of episodic memory - Norvilas, Algis (Psichologija, 2019)
In a series of four experiments, the cued-recall task was used to explore bilingual word representation in episodic memory. When target words were encoded singly, their recall to same-language and to crossed-language extralist cues was found not to be different. These results appear to support a language independent view of bilingual word representation in which words of different languages are mutually accessible. When target words were encoded in a cue-target relational fashion, recall of target words was much higher to original-language than to translated-language intralist cues, thus supporting a language dependent view. In this case information seems to be bound by the language in which it was originally encountered. This difference in results of cross-language cuing of singly and relationally encoded words was assumed to result from shifts in meaning brought about by contrasting word experiences. More broadly, the findings were interpreted within the context of Don Dulany’s (1997) mentalistic theory of evocative versus deliberative processing of words.